Strategic insights for sustainable conservation area development in TN Babul: SWOT and TOWS analysis approach (Journal of Social Economics Research, 2025)
The construction of the Maros–Watampone national road, which passes through the Bantimurung-Bulusaraung National Park (TN Babul), reflects a dilemma between the need for infrastructure development and environmental conservation in a tropical protected area. This area holds high ecological value as a habitat for various endemic and protected species, yet it is also targeted as part of a national strategic project. This study offers a strategic approach that combines SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the TOWS Matrix to develop adaptive and sustainable conservation area management strategies. SWOT analysis identifies internal and external factors in area management. The TOWS Matrix helps create practical and relevant strategic combinations. The analysis shows that TN Babul is in Quadrant II of the SWOT matrix. This highlights the need for diversification strategies to reduce internal weaknesses and capitalize on external opportunities. The novelty of this research lies in combining ecological, social, and institutional data to create evidence-based conservation strategies. The resulting strategies include adding green infrastructure to road design, improving data-driven biodiversity monitoring systems, supporting and educating local communities, and strengthening regulations and conflict risk management between people and wildlife. This approach not only provides technical solutions to the impacts of development but also proposes a transformation toward more participatory and inclusive conservation governance. This research makes a significant contribution to the development of data-based conservation policy models for protected areas under pressure from infrastructure development in Indonesia.